Update on the Pathophysiological Activities of the Cardiac Molecule Cardiotrophin-1 in Obesity - Mohamed Asrih; François Mach; Alessandra Quercioli; Franco Dallegri; Fabrizio Montecucco (Hindawi Limited, 2013)
Cardiotrophin-1 (CT-1) is a heart-targeting cytokine that has been reported to exert a variety of activities also in other organs such as the liver, adipose tissue, and atherosclerotic arteries. CT-1 has been shown to induce these effects via binding to a transmembrane receptor, comprising the leukaemia inhibitory factor receptor (LIFRβ) subunit and the glycoprotein 130 (gp130, a common signal transducer). Both local and systemic concentrations of CT-1 have been shown to potentially play a critical role in obesity. For instance, CT-1 plasma concentrations have been shown to be increased in metabolic syndrome (a cluster disease including obesity) probably due to adipose tissue overexpression. Interestingly, treatment with exogenous CT-1 has been shown to improve lipid and glucose metabolism in animal models of obesity. These benefits might suggest a potential therapeutic role for CT-1. However, beyond its beneficial properties, CT-1 has been also shown to induce some adverse effects, such as cardiac hypertrophy and adipose tissue inflammation. Although scientific evidence is still needed, CT-1 might be considered as a potential example of damage/danger-associated molecular pattern (DAMP) in obesity-related cardiovascular diseases. In this narrative review, we aimed at discussing and updating evidence from basic research on the pathophysiological and potential therapeutic roles of CT-1 in obesity.